DISTRIBUTED IP-BASED MOBILITY MANAGEMENT ACROSS WIRELESS MESH NETWORKS - SHAH, PEER AZMAT (2014)
A Wireless Mesh Network (WMN) has the ability to provide Internet services to end users through different network technologies like Ethernet, WLAN, WiMAX, GPRS etc. However, mobility of Mobile Nodes (MNs) across WMNs may cause service disruption and packet loss. Existing mobility management protocols are designed for single hop networks and are centralized in nature. This leads to single point of failure, long handover delays and control traffic overhead. Some multi-hop solutions have been proposed in literature but they only support intra WMN mobility. Even some of them can manage inter WMN mobility with the help of Mobile IPv6 but still the route optimization procedure of Mobile IPv6 causes higher handover delays and signalling overhead. The reason is that, the route optimization procedure of Mobile IPv6 used the return mutability procedure that performed the home address test and care-of-address test to check the reachability of MN at the home and care-ofaddresses.